Does size matter? Morphological and content analysis of the coprolites from a Quaternary deposit in the Iberian Peninsula - Irene Cambronero; Nuria García (Quaternary Environments and Humans)
Coprolites are very abundant in Quaternary deposits. However, they are often overlooked despite offering insights into both the surrounding environment and the species that produced them, particularly when skeletal remains are absent. We selected a Quaternary cave deposit from the Iberian Peninsula, Juan Labranz Cave, where an abundant and diverse coprolite collection was recovered, in order to develop a non-destructive study method that allows an accurate interpretation of the producer. Morphometric analyses of these specimens reveal two distinctive morphotypes associated with the two main carnivore occupations in the cave, hyaenas and bears. Morphotype I resembles hyaena coprolites in shape, texture, and bone inclusions, suggesting spotted hyaena as the most likely producer based on size. On the other hand, morphotype II deviates significantly, with a wrinkled texture and larger size, resembling bear faeces when eating carrion. Differences in bone fragment size and the presence of hair moulds further support these attributions. In conclusion, this study underlines the importance of considering taphonomy, morphology, size, and content in identifying coprolite producers, also high- lighting the relevance of these ichnofossils as indirect evidence of species and for the understanding of their ecological roles in Quaternary environments, where humans and other predators coexist.